An analysis of corpus from human computer exchanges using MSN Messenger - Goh, Ong Sing; Fung, Chun Che; Depickere, Arnold; Wong, Kok Wai (International Association of Engineers (IAENG), 2007)
In this paper, we report the collection and analysis of a corpus containing over 29,447 words, 2,541 unique words and 3,280 utterances in real instant messages exchanged between AINI conversational bots and 65 buddies human users. The results show that communication features differ significantly for conversation between human-human and human-machine in the Instant Message (IM) exchanges. The finding will provide guidelines for better design of future intelligent conversational bots for practical applications.